Linear Park: an urban planning tool to promote urban sustainability - Vitória, Tayná de Oliveira; Santos, Rosângela Leal; Chaves, Joselisa Maria (Scientific Journal ANAP, 2025)
Objective - This study aims to analyze the relevance of linear parks as urban planning instruments that promote urban sustainability by revitalizing water resources and providing spaces for recreation and environmental education. It is based on the hypothesis that linear parks are important green infrastructures that effectively contribute to sustainable urban development.Methodology - The research is grounded in a national and international theoretical review on the topic of linear parks, followed by critical analysis and interpretation of the findings to confirm or refute the proposed hypothesis. The methodology is qualitative and exploratory in nature, integrating theoretical references with normative and environmental aspects guiding the implementation of such spaces.Originality/relevance - The study contributes to contemporary debates on green infrastructure and sustainable cities, addressing an emerging topic within the Brazilian context. It starts from the observation that, although Brazil possesses a large amount of natural resources in urban areas, these are often neglected, while public demand for leisure spaces is growing. Linear parks, internationally recognized as integrative urban tools, emerge as viable solutions for reconciling environmental conservation with urban quality of life.Results - It was found that linear parks, often located in valley bottoms and associated with watercourses, are frequently designated as Permanent Preservation Areas (APP) under Brazilian environmental law. However, there is no single method for their implementation, as each case must be adapted to the physical, biotic, and anthropic characteristics of the area and to the involvement of the local community. A key guideline identified is the need to start from a comprehensive planning process, including a complete diagnostic of the area and public engagement from the outset.Theoretical/methodological contributions - The article contributes to consolidating the discussion on linear parks as sustainable urban planning tools. Methodologically, it highlights the importance of interdisciplinary diagnostics and participatory management as guiding principles, proposing technical and social criteria that can support future urban interventions with an environmental focus.Social and environmental contributions - The findings suggest that linear parks have the potential to restore degraded urban ecosystems, expand the availability of accessible green areas, and promote environmental education, thus strengthening the relationship between society and nature. By combining preservation and leisure, these green infrastructures directly support socio-environmental equity and the improvement of urban quality of life.
Keywords: Greenway; Urban intervention; Green infrastructure